RELATIVE ABUNDANCE OF SCIAENIDS ALONG ANDHRA-ORISSA COAST - Rao, T Appa (Indian Journal of Fisheries, 2011)
A variety of species of sciaenids are known to occur along the east andwest coasts of India (Lai Mohan 1969) where these form one of the commonestof groups in the fish catches. From the west coast, Hefford (1949), Jayaramanet al (1959) and Rao (1965) have dealt with the distribution, relativeabundance and catch trends of 'ghol' (Pseudosciaena diacanthus). Along theeast coast, knowledge regarding the distribution and abundance of sciaenids islacking. They contribute 10-15% of the total catches in the Government ofIndia trawlers operated from Visakhapatnam. Studies on the distribution ofsciaenids, occurring along the Andhra and Orissa coasts were taken up by theauthor and the present paper reports the results of investigations carriedout on the basis of the data of M.T. Ashok during the period from 1964 to1970 and of M.V. Champa during 1964-1971.